REKAYASA PERANGKAT LUNAK PEMESANAN TIKET BIOSKOP BERBASIS WEB - Ganda Yoga Swara, M.Kom; Yunes Pebriadi (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2016)
Cinema contitute effort that work in giving fervice like entertainment to peoples. Implementation of ticket in the cinema, still doing by conventional and not efficient. Mamy people come make place to buy a tickep unable to handle it make many people waste time only to wait shift to buy a ticket. Application that make in the final project to make people easier to booking flace and share film that they wanp to fee with thif application I hope can give system customer service so need tecnology information for make easier the way information so that process that we do can be more effective and efficient. Thif application making with web and MySQL as place to save the data.